MAX-PLUS ALGEBRA MODEL ON INAPORTNET SYSTEM SHIPS SERVICE SCHEME - Nurwan, Nurwan; F. Payu, Muhammad Rezky (PATTIMURA UNIVERSITY, 2022)
Queues are often found in public service providers, including port services. Therefore, the InaPortNet scheme was developed to facilitate and minimize queues in and out of ships. Also, service performance was optimized through behavior analysis and queuing system stability. This study focused on designing the max-plus algebra model and time estimation on the incoming ship service scheme. The results showed that the InaPortNet system is useful for modeling. Furthermore, the max-plus algebra matrix is used to obtain an estimated service time from registration to the ship docking process at the port. However, further study needs to be carried out by scheduling the max-plus algebraic matrix in order to analyze the behavior and stability of the queuing system